Strengthening Cooperation between TNI and Polri in Improving Law Enforcement Performance in Indonesia - Rudy Cahya Kurniawan (The Indonesian Journal of International Clinical Legal Education, 2023)
Law enforcement, encompassing various facets, constitutes a professional domain. The attainment of the title police officer mandates individuals to undergo comprehensive training and education, acquiring intellectual, theoretical, and technical proficiency. Upon completion, they integrate into a structured organization, adhering to specific disciplines and a code of ethics outlined by the profession itself. Crucially, a commitment to public service is a fundamental tenet upheld by all members of the police profession. This study employs an empirical juridical approach to investigate the legal principles governing the Indonesian National Police (TNI-Polri). The empirical juridical method is employed to analyze the applicable legal frameworks, particularly those pertaining to the TNI-Polri. The endeavor to enhance the professionalism of the Indonesian National Police involves strategic, organizational, and programmatic levels. Challenges encountered in this pursuit include the prevalence of negative public perceptions towards the National Police, as well as constraints related to budgetary limitations and inadequate infrastructure for implementing cooperative strengthening programs.